An AMC Backed Folded Dipole Slot Antenna Based on CMOS Process - Guo Qing Luo; Lin Qi Wu; Xiao Hong Zhang (International Journal of Antennas and Propagation)
A fold dipole slot antenna backed by artificial magnetic conductor (AMC) structure based on a standard 0.18 um CMOS process on chip application is firstly proposed in this paper. Conventional silicon antenna on chip (AoC) suffers from low radiation performance because the most electromagnetic energy is restricted in silicon substrate as surface wave for its high dielectric permittivity. The energy is dissipated as thermal for low resistivity of silicon substrate. AMC constructed by a periodic 6*6 square patch array is adopted as background to improve radiation performance of the proposed folded dipole slot AoC. Gain of the proposed AMC backed AoC is improved about 3.5 dB compared with that of the same AoC without AMC background.